O Pacto Nacional pelo Fortalecimento do Ensino Médio no Colégio Estadual Dona Leonor Calmon da rede pública do estado da Bahia - Cerqueira, Alessandra Adelina Santos (2018)
The National Pact for the Strengthening of Secondary Education is a public policy program implemented in 2013 by the federal government, whose purpose was to promote improvements in Brazilian Basic Education. Summarized by Pacto, the Program has been focused on the continuing education of teachers based on the development of pedagogical practices consonant with the integral human education of the students, a perspective pointed out by the National Curricular Guidelines of the Secondary School. It should be noted that the Pact corresponds to an educational policy focused on the training of teachers involving Brazilian universities and the pedagogical and administrative structure of public state primary education networks, seeking to significantly affect the transformation of teaching practices. The present research investigates the results in the State of Bahia of the actions promoted by the Pact, focusing on the teacher training course held in the period from March to December 2014 at the Dona Leonor Calmon State College, located in the capital Salvador. The objective of the research is to analyze the changes identified in the teaching practice from the training course, using the following guiding question: in what sense the training presented by the Pact led to the re-signification of the pedagogical practices and to the improvement of the development of the students of the Teaching Average at the school investigated? The study is carried out on an analytical horizon that takes into account the historical components of public policies aimed at secondary education in Brazil, showing how LDB 9394/1996 gave rise to the assumptions that led to the proposal of the Pact in 2013. The methodological basis adopted is that of qualitative research, using bibliographical and documentary input, as well as the application of semi-structured interviews to the teachers of the investigated school unit. The interpretation of the diversified discourses collected through the interviews is carried out through the set of methodological tools that make up the Content Analysis as proposed by Bardin (2004). The results presented here show that the Pact had broad participation in terms of the participation of the subjects involved, but its repercussion in the concrete transformation of pedagogical practices did not satisfactorily reach the proposed objectives, which makes it necessary for Brazil to adopt in the future new policies that take into account the experience gained.